Electroconvulsive therapy enhances endocannabinoids in the cerebrospinal fluid of patients with major depression: a preliminary prospective study - Kranaster, Laura; Hoyer, Carolin; Leweke, F. Markus; Janke, Christoph; Thiel, Manfred; Sartorius, Alexander (European archives of psychiatry and clinical neuroscience, 2017)
Despite the lack of clinical data about the role of the endocannabinoid system (ECS) in affective disorders, preclinical work suggests that the ECS is relevant in both with regard to the etiology of depression as well as the mediation of antidepressant effects. We measured the intraindividual levels of the endocannabinoids N-arachidonoylethanolamine (AEA) and 2-arachidonoylglycerol (2-AG) in the cerebrospinal fluid of 12 patients suffering from a major depressive episode before and after the antidepressant treatment by electroconvulsive therapy (ECT). AEA was significantly elevated after ECT as compared to baseline. The AEA increase positively correlated with the number of individually performed ECT sessions. Although the sample size was small and confounders were not rigorously controlled for, our finding corroborates preclinical work and should encourage further exploration of the involvement of the ECS in depressive disorder.
First online: 24 March 2017
Gesehen am 06.06.2018